ELM behavior in ASDEX Upgrade with and without nitrogen seeding. (30th September 2016) - Frassinetti, L.; Dunne, M.G.; Beurskens, M.; Wolfrum, E.; Bogomolov, A.; Carralero, D.; Cavedon, M.; Fischer, R.; Laggner, F.M.; McDermott, R.M.; Meyer, H.; Tardini, G.; et al.
Abstract: The Type I ELM behavior in ASDEX Upgrade with full W plasma facing components is studied in terms of time scales and energy losses for a large set of shots characterized by similar operational parameters but different nitrogen seeding rate and input power. ELMs with no nitrogen can have two typical behaviors, that can be classified depending on their duration, the long and the short ELMs. The work shows that both short and long ELMs have a similar first phase, but the long ELMs are characterized by a second phase with further energy losses. The second phase disappears when nitrogen is seeded with a flux rate above 10 22 (e s −1 ). The phenomenon is compatible with a threshold effect. The presence of the second phase is related to a high divertor/scrape-off layer (SOL) temperature and/or to a low pedestal temperature. The ELM energy losses of the two phases are regulated by different mechanisms. The energy losses of the first phase increase with nitrogen which, in turn, produce the increase of the pedestal temperature. So the energy losses of the first phase are regulated by the pedestal top parameters and the increase with nitrogen is due to the decreasing pedestal collisionality. The energy losses of the second phase are related to the divertor/SOL conditions. The long ELMs energy losses increase with increasing divertor temperature and with the number of the expelled filaments. In terms of the power lost by the plasma, the nitrogen seeding increases the power losses of the short ELMs. The long ELMs have a first phase with power losses comparable to the short ELMs losses. Assuming no major difference in the wetted area, these results suggest that (i) the nitrogen might increase the divertor heat fluxes during the short ELMs and that (ii) the long ELMs, despite the longer time scale, are not beneficial in terms of divertor heat loads.